The goonies - Donner, Richard; Bernhard, Harvey, 1924-; Spielberg, Steven, 1946-; Columbus, Chris; Antin, Steven, 1958-; Trainor, Mary Ellen; Pantoliano, Joe.; Feldman, Corey; Brolin, Josh.; Quan, Jonathan Ke, 1971-; Green, Kerri, 1967-; Ontiveros, Lupe.; et al. (Burbank, CA : Distributed by Warner Home Video, 2007)
Two kids find a treasure map just as they're about to lose their house. They and their friends go on a search for the treasure, but not without trouble from a few ne'er-do-wells.
Special features: Commentary (with hidden video treasures) by director Richard Donner and selected cast members; outtakes; new featurette "The making of The goonies;" Cyndi Lauper "The goonies 'r' good enough" music video; theatrical trailer.
DVD, region 1, widescreen (letterbox, enhanced) presentation; Dolby Digital 5.1 surround, Dolby Digital stereo. surround, Dolby Digital mono., dual-layer.
Title from container.
Originally released as a motion picture in 1985.
Music, Dave Grusin.
Steven Antin, Mary Ellen Trainor, Joe Pantoliano, Corey Feldman, Josh Brolin, Ke-Huy Quan, Kerri Green, Lupe Ontiveros, Martha Plimpton, Newt Arnold, Robert Davi, Sean Astin, Anne Ramsey.
MPAA rating: PG.
Keywords: Friendship in children -- Drama; Adventure stories -- Drama; Treasure troves -- Drama; Amistad -- Teatro; Aventuras -- Teatro; Feature films; Action and adventure films; Thrillers (Motion pictures); Children's films; Video recordings for the hearing impaired; DVD-Video discs